ISLAMIC DEVELOPMENT MANAGEMENT PROGRAM IN THE INSTITUTIONS OF HIGH LEARNING WITH SPECIAL REFERENCE TO NEGARA BRUNEI DARUSSALAM - Yahaya, Mahayudin Hj (International Journal of Research -GRANTHAALAYAH, 2017)
This study examined the term of `Umran made by Ibn Khaldun in the 14th Century A.D. with the aim to compare with other terms, notably civilization and urbanization practiced by modern society in the context of development and management. The objective of the study is to identify the triangular theory of universal prosperity (ToUP/`Umran/) to be implemented according to the current situation and circumstances in line with the demands of Shari`a Law in Negara Brunei Darussalam. Among the focus of the study is the definition of ToUP, its resource, principles and ultimate goals for the welfare of human beings and universal prosperity. The study concludes that the Theory of Universal Prosperity is the base of the tree of all the problems that affect every aspect of human life whether in culture or civilization.